2021
DOI: 10.3390/jcm10153206
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Patterns in the First Trimester Diagnosis of Congenital Heart Disease

Abstract: Congenital heart disease (CHD) is the most common birth defect, with a reported prevalence of 5–12 per 1000 live births. Very recently, the American Institute of Ultrasound in Medicine published a guideline recommending the use of the four-chamber and the three-vessel and trachea views to screen for CHD in the first trimester of pregnancy. Our aim is to present abnormal image patterns that are seen in the four-chamber, three-vessel, and trachea views of the fetal heart in the first trimester and to describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…A recent meta-analysis showing that over half (56%) of fetuses affected by major cardiac pathology [ 44 ] are detected in the first trimester confirms this finding. It is hypothesized that if a structured protocol is followed with assessment of outflow tract views and color-flow Doppler imaging, detection rate will improve [ 44 , 45 ]. Another limitation emphasized by several studies is the high false-positive rate in the first trimester, since an anomaly identified in the first trimester may evolve or may be reclassified later in pregnancy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showing that over half (56%) of fetuses affected by major cardiac pathology [ 44 ] are detected in the first trimester confirms this finding. It is hypothesized that if a structured protocol is followed with assessment of outflow tract views and color-flow Doppler imaging, detection rate will improve [ 44 , 45 ]. Another limitation emphasized by several studies is the high false-positive rate in the first trimester, since an anomaly identified in the first trimester may evolve or may be reclassified later in pregnancy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sonographers experience and time allowed for a heart examination are among the most important factors that influence the ability to appropriately assess cardiac structures in the first trimester 26,50 . Botelli et al.…”
Section: How Accurate Is An Early Cardiac Examination?mentioning
confidence: 99%
“…Sonographers experience and time allowed for a heart examination are among the most important factors that influence the ability to appropriately assess cardiac structures in the first trimester. 26,50 Botelli et al identified human error as the primary cause of false negative diagnoses. 51 The lack of operator's adaptational skills (rather circumstantial aspects) mainly impacts correct appreciation of CHDs in the second trimester and it is likely that such factors similarly affect the early detection rate.…”
Section: Counseling After a Suspected Cardiac Anomaly In First Trimestermentioning
confidence: 99%
“…Важным аспектом является преобразование данных в диагностический алгоритм, чтобы сориентировать врачей относительно наиболее вероятного типа ВПС и правильной постановки диагноза для каждого отдельного случая [14].…”
unclassified